Lexical and Grammatical Metaphors in Newsweek - Sarah Nasution; Amrin Saragih; Busmin Gurning (LINGUISTIK TERAPAN, 2014)
This study investigates lexical and grammatical metaphors in Newsweek Weekly Magazines. The objectives of the study are to identify what lexical and grammatical metaphors used in Newsweek, to describe the way those metaphors are used, and to explain why the Newsweek use those lexical and grammatical metaphors. A qualitative descriptive research was applied. The data were taken from eight texts published on November and December in 2010. The data were collected by selecting the texts contained the issue of Barack Obama, The President of United States of America because of his visit to Indonesia on November. As the result, the use of lexical and grammatical metaphors has been found in Newsweek. The metaphors in Newsweek realized into four types of lexical metaphors and eight groups data of grammatical metaphor. The Newsweek used more grammatical metaphor than Lexical metaphor in order to make information contained in Newsweek it more coherent and compact, and to help readers more easily understand the information.   Keywords: metaphors; lexical; grammatical; mass media